2014
DOI: 10.1021/cm503033j
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Relationships of High-Electron Mobility Naphthalene Diimide Copolymers Prepared Via Direct Arylation

Abstract: Direct arylation (DA) is emerging as a highly promising method to construct inexpensive conjugated materials for large-area electronics from simple and environmentally benign building blocks. Here, we show that exclusive α-C–H selectivity is feasible in the DA of π-extended monomers having unsubstituted thiophene or furan units, leading to fully linear materials. Two new naphthalene diimide-based conjugated copolymers—P(FuNDIFuF4) and P(ThNDIThF4), composed of naphthalene diimide (NDI), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 60 publications
8
112
0
Order By: Relevance
“…As expected, the coefficients of the HOMO orbital are located on the SVS unit while that of the LUMO orbital is mainly positioned on the NDI unit, in good agreement with other NDI derivatives ( Figure S5, Supporting Information). [31,67] The dihedral angles between the NDI and SVS units are 47.70° and 43.78° ( Figure S5b, Supporting Information), which are larger than those reported for NDI and TVT, and NDI and bithiophene units, being 33.44° and 32.82°, and 32.88° and 40.61°, respectively. [66,68,69] The difference between the dihedral angles of these copolymers suggests a clear departure from extensive and continuous planarity in the polymer films with the most distorted being the PNDI-SVS copolymer.…”
Section: Synthesis and Density Functional Theory Calculationmentioning
confidence: 62%
See 1 more Smart Citation
“…As expected, the coefficients of the HOMO orbital are located on the SVS unit while that of the LUMO orbital is mainly positioned on the NDI unit, in good agreement with other NDI derivatives ( Figure S5, Supporting Information). [31,67] The dihedral angles between the NDI and SVS units are 47.70° and 43.78° ( Figure S5b, Supporting Information), which are larger than those reported for NDI and TVT, and NDI and bithiophene units, being 33.44° and 32.82°, and 32.88° and 40.61°, respectively. [66,68,69] The difference between the dihedral angles of these copolymers suggests a clear departure from extensive and continuous planarity in the polymer films with the most distorted being the PNDI-SVS copolymer.…”
Section: Synthesis and Density Functional Theory Calculationmentioning
confidence: 62%
“…[30] Similar efforts have been devoted to improving n-channel polymer semiconductors, with the performances of n-type devices still lagging behind their p-channel counterparts. [31][32][33][34][35][36] The main obstacle that has traditionally prevented the improvement of electron transporting polymers is the presence of trap sites forming at around −3.8 to −4.0 eV, mainly associated with hydrogenated oxygen, which complicates the design of conjugated polymers because of the requirement for a lowest unoccupied molecular orbital (LUMO) energy level that lays below this range. [37] In the recent past, different solutions have been proposed, among which a remarkably well performing solution-processable n-type polymer reported by Yan et al, based on a naphthalene diimide (NDI) acceptor moiety (referred to as PNDI2OD-T2) and easily achieving fieldeffect mobilities in the 0.1 to 1 cm 2 V −1 s −1 range, represented a breakthrough in the development of n-channel organic polymeric semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions have previously been used for the successful copolymerization of F 4 Br 2 and naphthalene diimide-based monomers which are structurally similar to DPPTh 2 . 31 Parameter screening was generally accompanied by isolated polymer yields after Soxhlet extraction, size exclusion chromatography (SEC), and high-temperature 1 H NMR spectroscopy. All entries of DAP reactions are compiled in Table 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…While a detailed spectroscopic analysis of this side reaction is yet to be related to a broad variety of reactions conditions, it is clear from our studies that typical side reactions during DAP are rather related to homocouplings and chain end degradation (either through dehalogenation or through reaction via C−H activation of the solvent) than to unselective C−H activation. 26,31,32 Next, we turned to the most interesting question as to what extent the used reaction conditions were responsible for undesired DPPTh 2 homocouplings. In a previous study, we observed that the presence of PCy 3 as ligand and PivOH/ K 2 CO 3 instead of KOPiv was important to suppress homocouplings of the C−H monomer.…”
Section: Macromoleculesmentioning
confidence: 99%
“…On the other hand, direct C-H arylation polymerization has attracted much attention because it presents an economically and ecologically attractive alternative to the traditional cross-coupling reactions. [26][27][28][29]38,39,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] Recently, the application of directly arylated polymers to the preparation of OPVs has been investigated. 45,54,55 In this study, we report the synthesis and characterization of double acceptor copolymers, -(CPDT-TPD-CPDT-BT) n -, comprising TPD, BT and two CPDT units in the polymer-repeating unit (Figure 1).…”
Section: Introductionmentioning
confidence: 99%